Relative growth of Uca burgersi (Crustacea, Ocypodidae) from two mangroves in the southeastern Brazilian coast - Benetti, Aline Staskowian [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2004)
The relative growth of the fiddler crab Uca burgersi Holthuis, 1967 was analyzed in two populations from different mangroves (Ubatumirim and Cavalo rivers) in the southeastern Brazilian coast, monthly sampled from May, 2001 to April, 2002. The population from a high productivity level mangrove reaches the sexual maturity in larger sizes than the population from a less productive site. This results can be attributed to the greater amount of nutrients found in the Cavalo than in Ubatumirim mangrove.
Keywords: Relative growth; Uca; size maturity; mangrove